The use of synchrotron X-rays and ultrasonics for investigating the bubble size distribution and its evolution in bread dough. (November 2017) - Koksel, Filiz; Strybulevych, Anatoliy; Aritan, Serdar; Page, John H.; Scanlon, Martin G.
Abstract: The feasibility of using ultrasound as a tool for quantitatively measuring dough's bubbly microstructure was explored. The bubble size distribution (BSD) and its evolution due to disproportionation in non-yeasted doughs were characterized at the micron scale using synchrotron X-rays. Concurrently, measurements of the phase velocity and attenuation coefficient were performed using an ultrasonic transmission technique. An ultrasonic model based on propagation of sound waves in media with polydisperse scatterers was used to predict the wave vector from bubble microstructure definitions obtained microtomographically and compare it with the wave vector from measurement of velocity and attenuation. Correspondence was good across most of the frequency range, but a discrepancy between measured ultrasonic parameters and predictions from the model was observed in the low frequency region. A consideration of how resonating bubbles are sensitive to local rheological properties of the dough matrix was proposed as an important constituent for the ultrasonic model. Excellent predictions of the measured ultrasonic parameters were then attained across all frequencies. These results therefore show the potential of ultrasonic techniques for determination of BSDs in dough and their evolution, opening up the possibility of comprehensive in situ investigations of the mechanisms governing changes in dough's aerated structure during breadmaking. Highlights: Bubble size distributions in dough were characterized using synchrotron X-rays. Ultrasound was used to probe the changes in bubbly structure of doughs. An ultrasonic model was assessed for monitoring dough microstructure in situ. Bubble resonance is sensitive to local rheological properties of the dough matrix. The ultrasonic model potentially enables measurements of bubble size evolution.